A challenging modified measles outbreak in vaccinated healthcare providers - Omar Zmerli; Amanda Chamieh; Eliane Maasri; Eid Azar; Claude Afif (Elsevier, 2021)
Summary: Background: Modified measles is rarely reported and thought to be an attenuated, less transmissible form of measles. The occupational safety and management of previously immunized healthcare providers (HCP) facing the global reemergence of measles is controversial and unclear.Aim: We report a measles outbreak with an unusual presentation among our vaccinated HCP at Saint George Hospital University Medical Center (SGHUMC) in Lebanon that occurred during a nationwide measles epidemic. Methods: We recorded cases at SGHUMC, a 333-bed tertiary-care center, from April 2018 to June 2018. We established a measles clinic for investigating all febrile patients. HCP exposure was linked to influx of index cases through our Emergency Department. Modified measles was defined as any variation in the classic presentation with a pinpoint/vesicular rash, documented exposure and evidence of prior immunity. We performed serology testing to diagnose and/or document immunity and implemented outbreak controls measures including PPE, airborne isolation, and mass notification. Findings: We diagnosed 8 inpatients with classic measles, and 9 affected HCP. We diagnosed 8 HCP with modified measles. One previously immunized HCP developed classic measles despite being immunized and having a positive IgG titer. Our contact tracing revealed a total of 96 exposed HCP with 27 HCP showing non-specific signs of viral illness. We required all the 9 affected HCP to undergo home isolation. Conclusion: We believe it is a top priority to achieve adequate measles immunity, especially among HCP that are at the frontline of healthcare systems. This necessitates revisiting vaccination schedules and achieving seroprotective titers to reclaim proper herd immunity.